Anomalous High‐Temperature Superconductivity in YH6. Issue 15 (10th March 2021) - Troyan, Ivan A.; Semenok, Dmitrii V.; Kvashnin, Alexander G.; Sadakov, Andrey V.; Sobolevskiy, Oleg A.; Pudalov, Vladimir M.; Ivanova, Anna G.; Prakapenka, Vitali B.; Greenberg, Eran; Gavriliuk, Alexander G.; Lyubutin, Igor S.; Struzhkin, Viktor V.; et al.
Abstract: Pressure‐stabilized hydrides are a new rapidly growing class of high‐temperature superconductors, which is believed to be described within the conventional phonon‐mediated mechanism of coupling. Here, the synthesis of one of the best‐known high‐ TC superconductors—yttrium hexahydride I m 3 ¯ m ‐YH6 is reported, which displays a superconducting transition at ≈224 K at 166 GPa. The extrapolated upper critical magnetic field B c2 (0) of YH6 is surprisingly high: 116–158 T, which is 2–2.5 times larger than the calculated value. A pronounced shift of T C in yttrium deuteride YD6 with the isotope coefficient 0.4 supports the phonon‐assisted superconductivity. Current–voltage measurements show that the critical current I C and its density J C may exceed 1.75 A and 3500 A mm −2 at 4 K, respectively, which is higher than that of the commercial superconductors, such as NbTi and YBCO. The results of superconducting density functional theory (SCDFT) and anharmonic calculations, together with anomalously high critical magnetic field, suggest notable departures of the superconducting properties from the conventional Migdal–Eliashberg and Bardeen–Cooper–Schrieffer theories, and presence of an additional mechanism of superconductivity. Abstract : Novel yttrium hexahydride YH6 is synthesized, an outstanding high‐ T C superconductor with critical temperature of 224–226 K and unexpectedly large upper critical magnetic field ≈116–158 T. YH6 demonstrates high critical current density of ≈3500 A mm −2 at 4 K, which is above that of NbTi and YBCO. This study points to a possible additional nonconventional contribution to superconductivity in YH6 .